Optimization of Mixed Cultivation of the Moderate Thermophilic Bioleaching Microorganisms for High Cell Density Using Statistical Methodology. Issue 3 (16th March 2019) - Zhou, Wenbo; Wu, Junzi; Zeng, Weimin; Wang, Yuguang; Guo, Ning; Zhang, Lijuan; Wan, Lili; Zhou, Hongbo
Abstract: The low functional microbial population density in the industrial bioleaching process has been a limiting factor for the high leaching efficiency, making the microbial cultivation and continuous inoculation an alternative for sustaining the microbial activity. In the present experiment, the defined mixed cultivation of Leptospirillum ferriphilum YSK, Sulfobacillus acidophilus TPY, Acidithiobacillus caldus S2, and Ferroplasma thermophilum L1 was evaluated and optimized by Statistical Methodology. Going through the Plackett–Burman experimental design, pH value, temperature, and c(MgSO4 ·7H2 O) were considered as the most significant factors in the defined range. Then, the relationships were analyzed using the steepest ascent design, the central composite design, and finally the response surface methodology. It was suggested that the optimum parameters were pH 1.38, MgSO4 ·7H2 O 0.552 g/L, temperature 44 °C, FeSO4 ·7H2 O 40 g/L, sulfur 8 g/L, yeast 0.02% w/v, (NH4 )2 SO4 3g/L, K2 HPO4 0.5g/L, KCl 0.1g/L, Ca(NO3 )2 0.01 g/L, in which allowed total cell density of the microbial community to reach 7.63 × 10 8 cells/mL in the cultivation period. The lab experiments were routinely undertaken with the expectation that the L. ferriphilum YSK, S. acidophilus TPY, A. caldus S2, F. thermophilum L1 could rapid grown from initial cell density of 0.25 × 10 7 cells/mL to 2.82 × 10 8 cells/mL, 1.68 × 10 8 cells/mL, 2.76 × 10 8 cells/mL, 2.51 × 10 7 cells/mL, respectively in 58 h. It demonstrates a possibility to co-culture these microbes in a single reactor, providing an efficient way to regenerate of inoculation for biomining process.